2012
DOI: 10.5194/acpd-12-30589-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pervasive and persistent Asian dust event over North America during spring 2010: lidar and sunphotometer observations

Abstract: Among the many well-documented cases of springtime trans-Pacific transport of crustal dust from Asia to North America (significant events include those of 1998, 2001, and 2005), the events of March and April 2010 were extraordinary both in the extent of the dust distribution and in the unique meteorological conditions that caused the dust layers in the free troposphere to linger and be detectable across Canada and the Northern United States for over a month. This study focuses on extending previous research by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Interestingly, the spring Asian FD influence may have extended as far east as the Boundary Waters and Northeast regions, where a spring decoupling in FD and CM was also observed (Figure ). Asian dust impacts in the northeast previously have been observed [ Debell et al ., ; Cottle et al ., ], as well as dust transport from the Southwest [ Park et al ., ]. All regions in the East experienced a seasonal decoupling of FD and CM, with the mid‐South, Southeast, Appalachia, and Ohio River Valley regions having strong FD maxima in summer, likely associated with North African dust transport.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the spring Asian FD influence may have extended as far east as the Boundary Waters and Northeast regions, where a spring decoupling in FD and CM was also observed (Figure ). Asian dust impacts in the northeast previously have been observed [ Debell et al ., ; Cottle et al ., ], as well as dust transport from the Southwest [ Park et al ., ]. All regions in the East experienced a seasonal decoupling of FD and CM, with the mid‐South, Southeast, Appalachia, and Ohio River Valley regions having strong FD maxima in summer, likely associated with North African dust transport.…”
Section: Resultsmentioning
confidence: 99%
“…A suite of previous studies discussing source attribution of aerosol to long-range transport from Asia to North America have relied on NAAPS. For example, Cottle et al [ 31 ] used NAAPS with HYSPLIT back-trajectories, and sunphotometer and lidar data to show that springtime dust plumes from Asia reached North America. Wu et al [ 32 ], more recently, used NAAPS and remotely-sensed data from CALIPSO to study a trans-Pacific Asian dust event and its impact on the east coast of the United States.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Enough time is provided for the dust particles to externally and internally mix with other urban aerosols. Cottle et al [57] observed the maximum volume depolarization ratio within the dust layers reduced substantially from 0.27 over Vancouver to 0.15 over Egbert by the time the dust layers travelled across North America during April 2010. They explained this finding that was the result of continued loss of dust, external mixing with the background aerosol layer or more likely a combination of both.…”
Section: Comparisons Of Optical Properties Withmentioning
confidence: 99%